IMPLEMENTASI ARSITEKTUR BIOMIMETIK PADA DESAIN LIPONSOS KEPUTIH SURABAYA - Kosasih, Davin Nathaniel; Putra, Heristama Anugerah; Setiadi, Y.A Widriyakara (Jurnal Arsitektur ZONASI, 2023)
Liponsos Keputih Surabaya in 2016-2021 often experienced excess capacity, this was due to the excessive number of PMKS. This excess capacity is the main problem that causes the room and environment in Liponsos Keputih to become humid and stuffy, so that the level of comfort for residents, visitors and officers is very less to carry out activities at Liponsos. Therefore, it is necessary to redesign the Liponsos Keputih Surabaya by applying a biomimetic architectural approach that takes the characteristics of bamboo (a characteristic of the Keputih Surabaya area). The characteristic taken as a design idea is the vertical growth of bamboo, so that the need for space and thermal can be fulfilled properly in the design. The method used in this research is Pahl and Beitz's Systematic Approach research method with qualitative data collection which is then presented by describing the data obtained. The final result, the redesign of Liponsos Keputih comes by applying a vertical pattern to the mass and a radial pattern to the site arrangement obtained from the transformation of bamboo plants. The outdoor space component is allocated for the needs of circulation, parking, sports fields, utility areas, and green open spaces.